Emotional intelligence 2.0 - Bradberry, Travis (San Diego Talent Smart, 2009)
In today's fast-paced world of competitive workplaces and turbulent economic conditions, each of us is searching for effective tools that can help us to manage, adapt, and strike out ahead of the pack.
Keywords: Emotional Intelligence